Notes on necrophagous flies (Diptera: Calyptratae) associated to fish carrion in Colombian Amazon (2010)
In recent years, there has been an increasing number of studies on carrion fly communities due to their medical importance and as a consequence of the large number of studies on forensic entomology. Surprisingly few studies have adressed with the asynantropic flies of the Amazon, and none were done in Colombia. A faunistic study of asynantropic flies of the families Calliphoridae, Sarcophagidae, Muscidae and Fannidae in three different landscapes of the Colombian Amazon is presented, trapping effectiveness is assessed, and the first record of Mesembrinella batesi (Aldrich, 1922) and Fannia femoralis (Stein, 1897) from Colombia is reported.